Can reported VaR be used as an indicator of the volatility of share prices? Evidence from UK banks. - Ou, Shian Kao (2006)
Value at Risk (VaR) is used as an indicator to measure the risks contained in a firm. With the uprising development of VaR theory and computational techniques, the VaR is nowadays adopted by banks and reported in annual reports. Since the method to calculate VaR is questioned, and the reported VaR can not be thoroughly audited, this paper attempts to find the relationship between the reported VaR and the volatility of share price for UK listed banks. This paper reviews literature about VaR and examine the financial reports of each banks. After testing the relationship through a regression model, it seems that the reported VaR has no significant relationship with the share price volatility.